2018
DOI: 10.3389/fmicb.2018.01312
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Process for Cadaverine Bio-Production Using a Consortium of Two Engineered Escherichia coli

Abstract: Bio-production of cadaverine from cheap carbon sources for synthesizing bio-based polyamides is becoming more common. Here, a novel fermentation process for cadaverine bio-production from glucose was implemented by using a microbial consortium of two engineered Escherichia coli strains to relieve the toxic effect of cadaverine on fermentation efficiency. To achieve controllable growth of strains in the microbial consortium, two engineered E. coli strains grown separately on different carbon sources were first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Although C. glutamicum showed higher tolerance to cadaverine, E. coli possesses a native cadaverine biosynthetic pathway, and the metabolism process and physiological role of cadaverine are relatively well studied in E. coli [ 38 ]. Nowadays, the highest titer of cadaverine obtained in engineered E. coli was performed by a consortium of two engineered E. coli, and 28.5 g/L of cadaverine was finally obtained [ 18 ]. Here, a lysine producing E. coli was chosen as the host strain in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. glutamicum showed higher tolerance to cadaverine, E. coli possesses a native cadaverine biosynthetic pathway, and the metabolism process and physiological role of cadaverine are relatively well studied in E. coli [ 38 ]. Nowadays, the highest titer of cadaverine obtained in engineered E. coli was performed by a consortium of two engineered E. coli, and 28.5 g/L of cadaverine was finally obtained [ 18 ]. Here, a lysine producing E. coli was chosen as the host strain in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the strain of C. glutamicum exhibited a higher tolerance to cadaverine, its growth rate was decreased by 67% in the presence of 102 g/L cadaverine. To mitigate the toxic effect of cadaverine in fermentative production, Wang et al [ 18 ] developed a synthetic microbial consortium consisting of two engineered E. coli strains , a l -lysine-producing strain and a 1,5-DAP-producing strain. These observations suggested that mitigating end-product inhibition would be useful for increasing cadaverine production.…”
Section: Introductionmentioning
confidence: 99%
“…Aer optimization of the culture conditions and multi-stage constant-speed feeding strategy, the microbial consortia cooperated well and exhibited high productivity of cadaverine (28.5 g L À1 ) during the fermentation process. 107 CO 2 is also the product aer the decarboxylation. The higher yield of cadaverine will result in releasing a higher amount of CO 2 , which is usually discharged like waste-gas in the benchscale experiment.…”
Section: Process Intensification For Cadaverine Productionmentioning
confidence: 99%
“…We recently made an attempt to find a cost-effective route to synthesize 1,5-diaminopentane (cadaverine) from 1,5-dibromopentane. On an industrial scale, this is produced by bacterial decarboxylation of lysine (Ma et al 2017;Wang et al, 2018). Attempts to react 1,5-dibromopentane with hmta in the presence of NaI in ethanol (modified from Galat & Elion, 1939) led to the crystallization of a monosubstituted product, 5-bromourotropinium bromide, C 11 H 22 BrN 4 + ÁBr À (1), the structure and supramolecular features of which are presented here.…”
Section: Chemical Contextmentioning
confidence: 99%